Unleashed : the phenomena of status dogs and weapon dogs - Harding, Simon (Criminologist) (Bristol : Policy, 2012)
The first book in the UK or US to set on record the recent cultural phenomenon of the use of certain dog breeds - both legal and illegal - to 'convey status' upon their owners.
Title from publisher's bibliographic system (viewed on 07 Sep 2022).
Keywords: Gangs -- Social aspects -- Great Britain; Dangerous dogs -- Great Britain; Crime -- Great Britain